Epidemiological study of alendronate-related osteonecrosis of the jaw in the southeast of Scotland. Issue 5 (June 2016) - Sammut, Stephanie; Malden, Nick; Lopes, Victor; Ralston, Stuart
Abstract: We aimed to establish the incidence of alendronate-related osteonecrosis of the jaw (ONJ) in the southeast of Scotland, and to assess the effect of corticosteroids on it. We studied a prospective case series of patients between June 2004 and March 2012 separated into steroid and non-steroid groups. There were 34 cases of alendronate-related ONJ and 78 732 drug patient years (DPY) of alendronate, making the overall occurrence 43.1 cases/100 000 DPY. There were 12 patients in the steroid group (mean (range) age 68.2 (48-87) years) making 42.5 cases/100 000 DPY, and 22 in the non-steroid group (mean (range) age 76.2 (63-91) years) making 119.6 cases/100 000 DPY. The mean (range) age at presentation of alendronate-related ONJ was significantly lower in the steroid group (68.2 (48-87) compared with 76.2 (63-91) years, p = 0.019) as was the duration of exposure to alendronate before it developed (28.9 (6-120) compared with 61.3 (13-168) months, p = 0.03). The overall incidence seems to be higher in the southeast of Scotland than elsewhere. Concurrent use of corticosteroids is not associated with an increased incidence of alendronate-related ONJ, but it seems to reduce the duration of exposure before it develops. Age is likely to be a confounding factor.